2022
DOI: 10.1039/d2cp00343k
|View full text |Cite
|
Sign up to set email alerts
|

Cyclo[18]carbon including zero-point motion: ground state, first singlet and triplet excitations, and hole transfer

Abstract: Recent synthesis of cyclo[18]carbon has spurred increasing interest in carbon rings. We focus on a comparative inspection of ground and excited states, as well as of hole transfer properties of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Lambropoulos et al have studied the spectral properties of cyclo[18]carbon in its ground and excited states focusing on the effect of the zero-point vibrations on the HOMO–LUMO gap and on the singlet–triplet excitation energies. 79 Yang and Cederbaum 80 investigated the accommodation of guest atom Mg in carbon allotrope C 12 and have shown that the closed-shell global minimum with Mg atoms inside the ring acquires C 2v symmetry (the unperturbed C 12 has D 6h symmetry). Quite recently, Baryshnikov et al reported a computational DFT and CASSCF study on cyclo[ n ]carbons formed of an odd number of carbon atoms ( n = 5–29).…”
Section: Properties Of Cyclo[n]carbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lambropoulos et al have studied the spectral properties of cyclo[18]carbon in its ground and excited states focusing on the effect of the zero-point vibrations on the HOMO–LUMO gap and on the singlet–triplet excitation energies. 79 Yang and Cederbaum 80 investigated the accommodation of guest atom Mg in carbon allotrope C 12 and have shown that the closed-shell global minimum with Mg atoms inside the ring acquires C 2v symmetry (the unperturbed C 12 has D 6h symmetry). Quite recently, Baryshnikov et al reported a computational DFT and CASSCF study on cyclo[ n ]carbons formed of an odd number of carbon atoms ( n = 5–29).…”
Section: Properties Of Cyclo[n]carbonsmentioning
confidence: 99%
“…Lambropoulos et al have studied the spectral properties of cyclo [18]carbon in its ground and excited states focusing on the effect of the zero-point vibrations on the HOMO-LUMO gap and on the singlet-triplet excitation energies. 79 Yang and Cederbaum 80 81 Analysing the magnetically induced ring currents, they showed, in analogy with even numbered cyclo[n]carbons, that 4k + 3 rings exhibit an aromatic character, while the 4k + 1 rings are anti-aromatic. Another computational study pinpointing the route to cyclo [18]carbon from two possible precursors (C 18 Br 6 and C 18 (CO) 6 ) was performed using the nudged elastic band method 82 and authors have shown that applying the electric field to the anion of the former precursor lowers the activation barrier to 72 kJ mol À1 .…”
Section: Properties Of Cyclo[n]carbonsmentioning
confidence: 99%
“…A similar conclusion was reached by Lambropoulos et al, who found that ZPR in cyclo [18]carbon can be reduced to the effect of a few bond-stretching vibrational modes. 12 In organic molecular wires, bond stretching and backbone torsion play a large role, as the electron and hole mobilities are highly dependent on the extend of conjugation modulated by these vibrations. [13][14][15] In more general cases, it can be challenging to understand which vibrations are important and which can be neglected.…”
mentioning
confidence: 99%
“…A similar conclusion was reached by Lambropoulos et al, who found that ZPR in cyclo [18]carbon can be reduced to the effect of a few bond-stretching vibrational modes. 12 In organic molecular wires, bond stretching and backbone torsion play a large role, as the charge-carrier mobilities are highly dependent on the extent of conjugation modulated by these vibrations. [13][14][15] In more general cases, it can be challenging to understand which vibrations are important and which can be neglected.…”
mentioning
confidence: 99%